Reinterpreting the Islamic Sufi Calendar: The Science of Letters in the Hijri Calendar between Ṭarīqah Qādiriyah and Ṭarīqah Qādiriyah Naqshbandiyah - Riyanto, Waryani Fajar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
There are twelve names of the months in the Islamic Hijrī Calendar, i.e., Muḥarram, Ṣafar, Rabī‘ al-Awwal, Rabī‘ al-Ākhir, Jumād al-Ūlā, Jumād al-Ākhir, Rajab, Sha‘bān, Ramaḍān, Syawwāl, Dhū al-Qai’dah, and Dhū al-Ḥijjah. Although this is an exhaustively discussed topic, it is quite rare to analyze it using the perspective of the Science of Letters (‘Ilm al-Ḥurūfī). Two reputable Sufi ṭarīqah that interpreted the meanings in Sufism of every letter composing the names of the Hijrī months are Ṭarīqah Qādiriyah (TQ) and Ṭarīqah Qādiriyah Naqshbandiyah (TQN), respectively represented by Shaykh ‘Abd al-Qādir al-Jīlānī (Jīlānī) and Muḥammad ‘Abd al-Gaos Sayfullāh Maslūl (Gaos). In light of this, the current paper discusses the comparison between TQ and TQN by exploring Jīlānī and Gaos’ thoughts on the Science of Letters in the Hijrī Calendar. This article employed a qualitative approach and utilised original data sources from the treatises of Jīlānī, titled al-Ghunyah, and from Gaos, titled Faḍā’il al-Shuhūr. This study is distinctive as four methods were used in its analyses, i.e., comparison, the Science of Letters (‘Ilm al-Ḥurūfī), mystical trio relations (Allāh-Muḥammad-Mu’min/Rajab-Sha‘bān-Ramaḍān), and triangulation of experts in Sufi thoughts. This article proposes an Islamic Sufi Calendar based on the Science of Letters in the Hijrī Calendar. The findings of this study have implications for a deeper understanding of the Sufi meanings behind the names of Hijrī months.